Tongue spindle cell rhabdomyosarcoma: case report in a pediatric patient - Leal Cavalcante, Israel; da Silva Barros, Caio César; Cavalcante Carneiro Júnior, Helder; Medeiros Albuquerque, Assis Filipe; Agustin Vargas, Pablo; Barroso Cavalcante, Roberta; Benevenuto de Andrade, Bruno Augusto (Journal of Oral Diagnosis, 2025)
Rhabdomyosarcoma (RMS) is an uncommon soft tissue malignant tumor derived from striated muscle tissue. RMS is uncommon in the oral cavity. Herein, we reported the clinicopathological and immunohistochemical features of an RMS case in a 1-year-old female presenting clinically as an asymptomatic nodule on the lateral border of the tongue. The surgical excision of the lesion was performed. Morphologically, spindle cells with elongated nuclei and eosinophilic cytoplasm proliferation in a fascicular pattern was observed, with few tumor cells showing rhabdomyoblastic differentiation. Immunohistochemical analysis showed positivity to vimentin, muscle-specific actin, desmin, MyoD1, and myogenin. Ki-67 proliferation index was less than 10%. The final diagnosis was spindle cell RMS. The patient did not show signs of recurrence after twenty months of follow-up. Because of the unspecific clinical appearance, the clinical diagnosis of RMS is difficult. Therefore, careful histopathological and immunohistochemistry analysis of these tumors is essential for correct diagnosis and classification.